Green human resources management: A novel tool to boost work engagement - Baykal, Elif; Bayraktar, Osman (Frontiers in Psychology, 2022)
Increasing environmental awareness in business life has given way to Green Human Resources Management practices. The positive corporate image created by GHRM is encouraging for many employees and boosts their work engagement. GHRM practices make employees feel proud about their organization and creates a value-based ground for working in their current companies. Actually, internalized green inclinations of organizations, namely, value alignment between an organization and an employee, can make their employees feel greater psychological ownership about their companies, leading to greater engagement as it is suggested in social identity theory. Being inspired from psychological ownership literature, in this study, it is assumed that being exposed to Green Human Resources Management practices can make employees feel higher levels of work engagement and psychological ownership can have a mediator effect in this relationship. The model has been a tested model among 255 Turkish white-collar employees working in a manufacturing sector. Analyses have been carried out using the AMOS structural equation program and the PROCESS program. Results confirmed the above assumptions, confirming the assumptions of social identity theory and revealed the existence of mediator effect in the relationship between GHRM and work engagement of employees, illuminating the importance of GHRM for employees' positive attitudes toward their organization.